2016
DOI: 10.3354/ame01802
|View full text |Cite
|
Sign up to set email alerts
|

Rapid adaptation of predation resistance in bacteria isolated from a seawater microcosm

Abstract: Bacterial defense against protozoan grazing has been shown to occur in many different bacteria. Predation resistance traits may however be plastic, making bacterial com munities resilient or resistant to predation perturbations. We studied the adaptation of pre dation resistance traits in bacteria isolated from a microcosm experiment. In the initial microcosm ex periment the predation pressure on bacteria varied markedly, while changes in the bacterial community composition could not be verified. Seven bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…However, at both our sampling sites, the salinity was <5 psu, indicating that other environmental factors could have been of importance. Previous studies have shown that Duganella as well as Shewanella occur in both freshwater and brackish water ( Duganella : Rappé et al, 2000 ; Lin et al, 2019 ) ( Shewanella : Deng et al, 2014 ; Mathisen et al, 2016 ; Castillo et al, 2018 ). Both bacteria were isolated from brackish water, at a salinity of 0.9 and 4.4 psu, respectively, and the experiment was performed at a salinity of 3.5–4 psu.…”
Section: Discussionmentioning
confidence: 99%
“…However, at both our sampling sites, the salinity was <5 psu, indicating that other environmental factors could have been of importance. Previous studies have shown that Duganella as well as Shewanella occur in both freshwater and brackish water ( Duganella : Rappé et al, 2000 ; Lin et al, 2019 ) ( Shewanella : Deng et al, 2014 ; Mathisen et al, 2016 ; Castillo et al, 2018 ). Both bacteria were isolated from brackish water, at a salinity of 0.9 and 4.4 psu, respectively, and the experiment was performed at a salinity of 3.5–4 psu.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to rapidly gain predation resistance traits has been reported to be plastic and common among bacteria (Mathisen et al, 2016). Because the loss-of-function mutants of yjiC in predation-resistant B. licheniformis strains could not be obtained, an alternative strategy was used to investigate whether the predation resistance could be induced in the predation-sensitive strains Y071 and Y322 under the predatory pressure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We tested whether the predation-pressure on bacteria was a key factor for the occurrence of PRB. Predation-pressure on bacteria was calculated in two different ways: Ratio between the carbon biomasses of heterotrophic protozoa+eukaryotes and heterotrophic bacteria: Ratio between the carbon biomasses of heterotrophic protozoa and heterotrophic bacteria 72 , 73 : …”
Section: Methodsmentioning
confidence: 99%